DEVELOPMENT OF PRESENTATION MEDIA BASED ON PREZI IN FUNGI SUBJECT FOR GRADE X - Liya Indrawati; Endang Susantini; Ulfi Faizah (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2019)
Fungi  is  a  very  broad  topic.  Because  of  this  breadth,  learning  media  are  needed  so  it  can  help  students  to  understand  allfungi subject. The media needed can at least attract students' interest in studying fungi subject. One of suitable medium isPrezi-based  presentation  media  that  can  display  audio  and  visuals  in  delivering  material  and  also  can  be  zoomed  in  andzoomed  out  .  This  study  aims  to  produce  a  Prezi-Based  Presentation  Media  at  fungi  subject  in  grade  X  high  school  anddescribe  its  validity.  Media  development  is  done  at  Biology  Department,  Faculty  of  Mathematics  ans  Natural  Sciences,Universitas  Negeri  Surabaya  by  using  (ASSURE)  Analyze  Learner,  State Objective,  Select  Media and  Materials,  UtilizeMedia  and  Materials,  Require  Learner  Participation,  Evaluate  and  Revise  method.  The  media  validity  assessment  sheetrefers  to  the  Likert  scale.  The  media  is  reviewed  by  writing  down  whether  there  are  any  aspects  expected  in  eachcomponent  and  assessed  with  a  range  of  scores  from  1  to  4,  with  the  category  score  1  :  less  decent,  2  :  quite  decent,  3  :decent and 4 : very decent. The media was validated by two biology lecturers. Based on the results obtained, Prezi-basedpresentation media is declared decent with an average value of 3.28 and should be tested in terms of its validity.Keywords: Multimedia, Prezi, Fungi subject.